2016
DOI: 10.3892/mmr.2016.5211
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism-based microarray analysis for the diagnosis of hydatidiform moles

Abstract: In clinical diagnostics, single nucleotide polymorphism (SNP)-based microarray analysis enables the detection of copy number variations (CNVs), as well as copy number neutral regions, that are absent of heterozygosity throughout the genome. The aim of the present study was to evaluate the effectiveness and sensitivity of SNP-based microarray analysis in the diagnosis of hydatidiform mole (HM). By using whole-genome SNP microarray analysis, villous genotypes were detected, and the ploidy of villous tissue was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Morphologically, both complete mole and partial mole have distinct histopathological features; however, the subjective nature of the morphological characters may give rise to variation in diagnosis 33 . In particular when earlier evacuation is performed in the present ultrasound era, classic morphological features may be less distinct 34 . The differentiation between molar and non-molar gestations is usually clear in cases showing typical histological features, and in cases of complete mole this is confirmed by p57 immunohistochemistry 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Morphologically, both complete mole and partial mole have distinct histopathological features; however, the subjective nature of the morphological characters may give rise to variation in diagnosis 33 . In particular when earlier evacuation is performed in the present ultrasound era, classic morphological features may be less distinct 34 . The differentiation between molar and non-molar gestations is usually clear in cases showing typical histological features, and in cases of complete mole this is confirmed by p57 immunohistochemistry 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared to POC results of another group [12], the prevalence of wgUPD in our study was similar (0.47% vs. 0.5%), but the prevalence of triploidy in our study was lower (3.9% vs. 6.3%). Aside from the rare recurrent CHM with a biparental diploid karyotype, which is an autosomal recessive disease called familial recurrent HM (FRHM) due to biallelic mutations in 2 genes: NLRP7 at 19q13.42 [15] [16], and more rarely, KHDC3L at 6q13 [17], the genetic abnormalities associated with cases of triploidy with PHM, and the wgUPD associated with CHM can be reliably detected by oligo-SNP based CMA; correlation with clinical findings, histopathological features, p57 (KIP2) immunohistochemistry, and genotyping results may ensure accurate classification in equivocal cases [14].…”
Section: Discussionmentioning
confidence: 99%
“…Determination of the underlying etiology in such cases may be difficult without a molecular assay that can also detect UPD 11p, such as molecular genotyping with short tandem repeat (STR) loci, or an SNP-based CMA. Xie et al reported some cases of CHM and PHM that were not suspected by experienced obstetricians [14]. Those unsuspected cases were diagnosed with an SNP-based CMA; the detection of such unsuspected cases may prove vital to alert clinicians of the risk of those patients to develop GTN.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the present study is the largest and the first to report the uniparental disomic pattern of more than ten heterozygous CHMs in the entire genome. Some studies have used the SNP array to analyse hydatidiform mole 9,2531 . CHMs were used as a mono-haploid genomic source material 2528 .…”
Section: Discussionmentioning
confidence: 99%
“…CHMs were used as a mono-haploid genomic source material 2528 . The SNP array was used as a tool for villous classification 9,30,31 . Bug et al .…”
Section: Discussionmentioning
confidence: 99%